Optical and luminescent properties of MgAl2O4 ceramics doped with high level of Eu3+ ions concentrations; Optics and Spectroscopy; Vol. 141 - iss. 5 - Valiev D. T. Damir Talgatovich; Khasanov O. L. Oleg Leonidovich; Dvilis E. S. Edgar Sergeevich; Paygin V. D. Vladimir Denisovich; Lin Chaolu; Stepanov S. A. Sergey Aleksandrovich (2023, 2023)
The series of MgAl2O4 ceramics doped with high level of europium oxide (Eu2O3) up to 15 wt.% was fabricated by the Spark Plasma Sintering technique. The prepared ceramics have been tested using the various experimental techniques: X-ray diffraction, scanning electron microscopy, as well as optical and cathodoluminescence spectroscopy. The influence of europium oxide on the complex of optical and luminescent characteristics of 1300◦C ceramics is discussed. The nature of the luminescence centers and the luminescence decay parameters are considered in detail.